Social Responsibility Model based on The Thoughts of KH Ahmad Dahlan at Muhammadiyah Schools - Surianto, Moh Agung; Umaimah, Umaimah (Jurnal Tarbiyatuna, 2024)
There are still few social responsibility practices carried out by school institutions simultaneously, which integrate concern for employees, the poor, orphans and the environment as in the modern concept of Corporate Social Responsibility (CSR). This research aims to formulate a model for developing social responsibility in the Muhammadiyah Gresik charity business, especially in primary and secondary education, by referring to the thoughts of KH Ahmad Dahlan. Using a critical approach, this research seeks to develop a model of social responsibility based on the thoughts of KH Ahmad Dahlan, which has not been widely studied, especially in the Muhammadiyah environment. Data was collected through in-depth interviews, documentation, and focus group discussions (FGD). The results of the research show that the social responsibility program at the Gresik Muhammadiyah Primary and Secondary Education Institution is called School Social Responsibility (SSR), which includes four pillars: quality of service as worship, interaction with the environment (humans), concern for the planet earth , and make other schools partners. Philosophically, the SSR model is based on spiritual motivation, which has significant differences with the modern profit-oriented concept of CSR. Research on social responsibility in educational institutions is still new and limited, which is a new aspect in this research, considering that research on social responsibility is mostly carried out in profit-oriented companies. The contribution of this research can be a reference for a model for implementing social responsibility in other Muhammadiyah school institutions. For future research, a similar model can be developed in other Muhammadiyah organizations, such as universities, hospitals and non-profit organizations outside Muhammadiyah, both in Indonesia and other countries.